Peramalan Awal Harga Telur Ayam Ras di Indonesia Sebagai Pandangan Awal dalam Penentuan Kebijakan - Kautsar, Syahrizal (Politeknik Statistika STIS, 2023)
Food security is an issue that the world is currently facing. Indonesia's food security still needs to be improved. One of the factors that can affect food security is commodity prices. Broiler eggs are one of the important food commodities in Indonesia. This study modeled the consumer price of broiler eggs using clustering time series analysis and ARIMA modeling where the forecasting results can be used as an initial view in policy making. After analysis, it was found that the provinces of Indonesia can be grouped into three groups based on consumer price patterns of broiler eggs, namely into high, medium and low groups. Provinces in the high and low groups are predicted to experience stable prices at their respective levels. On the other hand, provinces in the moderate group are predicted to experience a trend of rising consumer prices for broiler eggs.